Detection of rotavirus‐ and norovirus‐specific IgG memory B cells in tonsils. Issue 2 (16th July 2018) - Sharma, Sumit; Hagbom, Marie; Nordgren, Johan; Frodlund, Jonas; Hinkula, Jorma; Ledin, Torbjörn; Svensson, Lennart
Abstract : Because rotavirus (RV) and norovirus (NoV) are transmitted through the fecal‐oral route, tonsils due to their location within the oropharynx may sample or become infected with these viruses. We investigated if RV and NoV RNA/antigen, or virus‐specific memory/plasma B cells can be detected in the tonsils. While neither RV/NoV antigen, nor genomic RNA was detected, 90% (27/30) of tonsils tested had RV‐ and NoV‐specific IgG memory B cells. However, the mechanism explaining how these cells get there (whether because of local induction or homing after induction at other sites) and the role these cells might play during active infection is not yet clear.